Short Message Service (SMS) Applications for Disease Prevention in Developing Countries - Déglise, Carole; Suggs, L. Suzanne; Odermatt, Peter (JMIR Publications, 2012)
BackgroundThe last decade has witnessed unprecedented growth in the number of mobile phones in the developing world, thus linking millions of previously unconnected people. The ubiquity of mobile phones, which allow for short message service (SMS), provides new and innovative opportunities for disease prevention efforts. ObjectiveThe aim of this review was to describe the characteristics and outcomes of SMS interventions for disease prevention in developing countries and provide recommendations for future work. MethodsA systematic search of peer-reviewed and gray literature was performed for papers published in English, French, and German before May 2011 that describe SMS applications for disease prevention in developing countries. ResultsA total of 34 SMS applications were described, among which 5 had findings of an evaluation reported. The majority of SMS applications were pilot projects in various levels of sophistication; nearly all came from gray literature sources. Many applications were initiated by the project with modes of intervention varying between one-way or two-way communication, with or without incentives, and with educative games. Evaluated interventions were well accepted by the beneficiaries. The primary barriers identified were language, timing of messages, mobile network fluctuations, lack of financial incentives, data privacy, and mobile phone turnover. ConclusionThis review illustrates that while many SMS applications for disease prevention exist, few have been evaluated. The dearth of peer-reviewed studies and the limited evidence found in this systematic review highlight the need for high-quality efficacy studies examining behavioral, social, and economic outcomes of SMS applications and mobile phone interventions aimed to promote health in developing country contexts.